Wolbachia pipientis: bacterial density and unidirectional cytoplasmic incompatibility between infected populations of Aedes albopictus. - Sinkins, S; Braig, H; O'Neill, S (1995)
Unidirectional cytoplasmic incompatibility is seen when certain Wolbachia-infected insect populations are crossed. Two hypotheses might explain this phenomenon: superinfections with mutually incompatible strains of Wolbachia producing incompatibility when crossed to individuals infected with only a single bacterial strain or, alternatively, a bacterial dosage model, with differences in Wolbachia densities responsible for the incompatibility. A quantitative PCR assay was set up as a general method to compare Wolbachia densities between populations. Using this assay in unidirectionally incompatible stocks of the mosquito Aedes albopictus, we have determined that densities are significantly higher in Houston than in the Mauritius and Koh Samui stocks. This is consistent with a dosage model for the observed crossing patterns, but does not rule out the possibility that superinfection is the primary cause of the incompatibility.